Application of indocyanine green fluorescence imaging navigation in pediatric surgery: A single-center review - Chiyoe Shirota; Akinari Hinoki; Takahisa Tainaka; Wataru Sumida; Satoshi Makita; Hizuru Amano; Aitaro Takimoto; Akihiro Yasui; Shunya Takada; Yoichi Nakagawa; Hiroo Uchida (Elsevier, 2023)
Background: Pediatric patients often exhibit congenital disorders and rare diseases. Consequently, pediatric surgeons must frequently perform atypical surgeries, dealing with a great deal of stress. Regarding atypical surgeries, navigation is required to ensure safety and surgical precision. In this study, we report our experience with 213 indocyanine green (ICG) fluorescence navigation (ICG-nav) surgeries and introduce our newly developed protocols of ICG-nav for pediatric surgery. Methods: The route and method of ICG administration, surgery, complications, and efficacy of ICG-nav surgery were retrospectively evaluated. Thereafter, the protocols were established. Results: Stable navigation was possible for chylothorax, cholelithiasis, primary hepatoblastoma lesions, hepatoblastoma lung metastases, nephroblastoma liver metastases, organ blood flow, the thoracic duct, lymphatic malformation, and lung segmentectomy. New protocols were established for these cases. Conclusions: ICG-nav could be performed safely in children given that the total amount of ICG administered was carefully controlled. Furthermore, ICG-nav was a highly applicable navigation surgical technique that could be used for treating a wide variety of diseases. To our knowledge, this is the first report of successful ICG-nav for liver metastases from nephroblastoma presented in this series.